Estudio del principio de progresividad de la norma y el derecho comparado en la legislación penal del delito de fraude deportivo, teniendo como detonante las grandes cifras económicas que se mueven dentro del entramado deportivo - Calle Jiménez, Christian Jonathan (2019)
The present thesis of degree deals with the title: "Study of the principle of progressiveness of the standard and the comparative right in the criminal legislation of the crime of sporting fraud, having as large the economic figures which move within the sports input;" legal problem of which I make my research object is that our criminal legislation (COIP), at the time of its publication in the official registry and after its entry into force promised and presumed to be a legislation that in addition to cutting edge put an end to criminal needs In our country. Of course, no norm is perfect, but if it is the work of our legislators who were elected precisely by popular will, look for solutions to problems or other needs that may be taken along the way in our legislation. Thus, our country suffers from great legal shortcomings in the criminal field, which have not yet been remedied by the legislature. Specifically, I have the theme of this, one of the issues that I consider a legal blunder such as the lack of the criminal type of sports fraud, which I consider of vital importance for our country. Ecuador in sports is at a great height, due to the outstanding participation of our athletes in the different disciplines, as a result of great feats and recognitions achieved worldwide, which place our country within the nations with outstanding athlete worldwide and with future projection. From the above it is evident that sports growth and the importance it means for Ecuador and in all areas of sport as well as political and even economic, should be regulated its development to foresee possible mishandling of the sport that entails irreversible damage, whether public or private.